«Вино покращує кров»: культура вина італійців Торонто - Дель Джудіче, Л. (Народна творчість та етнологія, 2012)
Luisa Del Giudice. «Wine Makes Good Blood»: Wine Culture Among Toronto Italians. The article highlights the folk technologies of wine producing and the traditions of its saving and drinking among Toronto Italian immigrants. The author investigates also beliefs, oral narrations about wine, winemaking, and the gastronomic-utopian country Cocain with the rivers of wine and mountains of food. The changes, that are taking place in recent years in producing and drinking of wine among Toronto Italians, are also analyzed.